Clinical characteristics of children evaluated for suspected pulmonary embolism with D-dimer testing. Issue 9 (8th November 2017) - Kanis, Jessica; Pike, Jonathan; Hall, Cassandra L; Kline, Jeffrey A
Abstract : Background: We sought to determine clinical variables in children tested for suspected pulmonary embolism (PE) that predict PE+ outcome for the development of paediatric PE prediction rule. Methods: Data were collected by query of a laboratory database for D-dimer from January 2004 to December 2014 for a large multicentre hospital system and the radiology database for pulmonary vascular imaging in children aged 5–17. Using explicit, predefined methods, trained abstractors, determined if D-dimer was sent in the evaluation of PE and then recorded predictor data which was tested for association with PE+ outcome using univariate techniques. Results: D-dimer was ordered in 526 children for clinical suspicion of PE. Thirty-four of 526 were PE+ (6.4%, 95% CI 4.3% to 8.7%). The radiology database identified 17 additional patients with PE (n=51 PE+ total). Children evaluated for PE were primarily in the ED setting (80%), teenagers (88%) and 2:1 female:male. Children with PE had higher mean heart and higher respiratory rate and a lower pulse oximetry and haemoglobin concentration. On univariate analysis, five conditions were more frequent in PE+ compared with no PE: surgery, central line, limb immobility, prior PE or deep vein thrombosis and cancer. Conclusions: The rate of PE diagnosis in children with D-dimer was 6.4%, similar to that seen in adults; most children with PE are over 13 years and had clinical predictors known to increase probability of PE in symptomatic adults. Future studies should use these criteria to develop a clinical decision rule for PE in children.